2021
DOI: 10.1186/s13613-020-00784-3
|View full text |Cite
|
Sign up to set email alerts
|

Ultraprotective ventilation allowed by extracorporeal CO2 removal improves the right ventricular function in acute respiratory distress syndrome patients: a quasi-experimental pilot study

Abstract: Background Right ventricular (RV) failure is a common complication in moderate-to-severe acute respiratory distress syndrome (ARDS). RV failure is exacerbated by hypercapnic acidosis and overdistension induced by mechanical ventilation. Veno-venous extracorporeal CO2 removal (ECCO2R) might allow ultraprotective ventilation with lower tidal volume (VT) and plateau pressure (Pplat). This study investigated whether ECCO2R therapy could affect RV function. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Despite also our meta‐regression evidenced that pre‐existing COPD affected the difference in TAPSE between COVID‐19 non‐survivors and survivors analysis, we additionally considered as moderating variables NIV and IMV. Indeed, as previously reported by different analyses, both the type and characteristics of respiratory support may influence the TAPSE estimation 29–31 . Therefore, the high heterogeneity observed in our analysis may be explained by the influence of pre‐existing COPD, the design of reviewed studies and associated inherited bias.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Despite also our meta‐regression evidenced that pre‐existing COPD affected the difference in TAPSE between COVID‐19 non‐survivors and survivors analysis, we additionally considered as moderating variables NIV and IMV. Indeed, as previously reported by different analyses, both the type and characteristics of respiratory support may influence the TAPSE estimation 29–31 . Therefore, the high heterogeneity observed in our analysis may be explained by the influence of pre‐existing COPD, the design of reviewed studies and associated inherited bias.…”
Section: Discussionsupporting
confidence: 52%
“…Indeed, as previously reported by different analyses, both the type and characteristics of respiratory support may influence the TAPSE estimation. [29][30][31] Therefore, the high heterogeneity observed in our analysis may be explained by the influence of pre-existing COPD, the design of reviewed studies and associated inherited bias.…”
Section: Discussionmentioning
confidence: 96%
“…54 articles were retrieved for full-text review, 21 of which were finally included in the systematic review and meta-analysis. These included three randomised controlled trials [8,17,18], totalling 531 patients, and 18 observational studies [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36], ranging from non-randomised controlled designs to retrospective cohort studies. Most studies were published in the past decade (n=15, 71%) [8,18,[24][25][26][27][28][29][30][31][32][33][34][35][36] and evaluated veno-venous ECCO 2 R (n=12, 57%) [8, 17, 19, 21, 27, 29-33, 35, 36].…”
Section: Resultsmentioning
confidence: 99%
“…These included three randomised controlled trials [ 8 , 17 , 18 ], totalling 531 patients, and 18 observational studies [ 19 36 ], ranging from non-randomised controlled designs to retrospective cohort studies. Most studies were published in the past decade (n=15, 71%) [ 8 , 18 , 24 36 ] and evaluated veno-venous ECCO 2 R (n=12, 57%) [ 8 , 17 , 19 , 21 , 27 , 29 33 , 35 , 36 ]. Studies were largely undertaken in Europe or North America.…”
Section: Resultsmentioning
confidence: 99%
“…Use of low flow extracorporeal CO 2 removal in moderate to severe ARDS has been recently shown to improve RV systolic function parameters implying that adequate CO 2 clearance potentially improves pulmonary hemodynamics. 13 Retrospective data (including data from the extracorporeal life support organization registry) has shown that initiation of VV ECMO in ARDS patients requiring vasoactive hemodynamic support resulted in a significant reduction in vasoactive drug doses with a low conversion rate to veno-arterial (VA) ECMO, possibly indicating RV unloading after commencement of VV ECMO. 14,15 The effect of invasive ventilation on pulmonary vascular resistance (PVR) and RV afterload in ARDS patients depends on its net effect on alveolar and extraalveolar vessels.…”
Section: Does Veno-venous Extracorporeal Membrane Oxygenationmentioning
confidence: 99%